The roles of child maltreatment and fathers in the development of substance use in an at-risk sample of youth: A longitudinal study. (August 2021) - Yoon, Susan; Kobulsky, Julia M.; Shin, Sunny H.; Coxe, Kathryn
Abstract: Background: Despite ample cross-sectional evidence linking child maltreatment and father involvement to adolescent substance use, little is known about the longitudinal impact of child maltreatment and father involvement in the developmental course of substance use from early adolescence to late adolescence. Objective: The primary aim of the study was to examine the long-term effects of childhood maltreatment (i.e., maltreatment type, perpetrator identity) and the quality and quantity of father involvement on developmental trajectories of substance use among high-risk youth. Participants and setting: Data were drawn from the Longitudinal Studies of Child Abuse and Neglect. Study participants included 681 U.S. adolescents who had experienced or were at risk for child maltreatment. Methods: Latent Growth Poisson Modeling was conducted to examine developmental trajectories of substance use at ages 12, 14, 16, and 18. Results: Child emotional abuse and greater quantity of father involvement were associated with a higher initial number of substances used, while higher quality of father-child relationships was associated with a lower initial number of substances used. Emotional abuse and greater quantity of father involvement were associated with slower increases in the number of substances used over time. Conclusions: The findings suggest that engaging fathers and promoting nurturing parenting and positive parent-adolescent interactions may be important for programs and policies aimed to prevent early adolescent substance use initiation. Furthermore, early identification of emotional abuse among adolescents could help to prevent initial polysubstance use onset.